ANALISIS PELAYANAN, FASILITAS, KEAMANAN, PENDAPATAN, DAN DAMPAKNYA TERHADAP MINAT WISATAWAN MENGUNJUNGI PANTAI BERKAS DI BENGKULU - Syamsul Huda; Jalal Ikhwan (Jurnal Ilmu Akuntansi, 2018)
The purpose of this study was to determine the effect of service, facility, a sense ofsafety, and impact on tourist interest to visit of Berkas beeach in Bengkulu. This studyuses a quantitative and qualitative analysis. Quantitative analysis using multiple linearregression. From these equations can be interpreted a constant value 4.314 hasmeaning if the coefficients of the independent variables consisting of service (X1) =0,427, facilities (X2) = 0,227, safety (X3) = 0,301, income (X4) = 0,372. Based on t-test,t values of security (X1) of 3,242, a sense of comfort (X2) is -1.371, information (X3) of2.091, income (X4) of 2.992.. The results of test calculations obtained F calculated Fvalue of 18.813, which means jointly significant effect between the independentvariable on the dependent variable Correelation coefisiencee (R) is 0,767 anddeterminant coefisience (R2) is 0,588, Mean, together impact are significant to touristinterest (Y).